2020
DOI: 10.1080/22221751.2020.1777906
|View full text |Cite
|
Sign up to set email alerts
|

Experimental aerosol survival of SARS-CoV-2 in artificial saliva and tissue culture media at medium and high humidity

Abstract: SARS-CoV-2, the causative agent of the COVID-19 pandemic, may be transmitted via airborne droplets or contact with surfaces onto which droplets have deposited. In this study, the ability of SARS-CoV-2 to survive in the dark, at two different relative humidity values and within artificial saliva, a clinically relevant matrix, was investigated. SARS-CoV-2 was found to be stable, in the dark, in a dynamic small particle aerosol under the four experimental conditions we tested and viable virus could still be detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
204
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(230 citation statements)
references
References 14 publications
7
204
0
2
Order By: Relevance
“…These results showed that the stability of SARS-CoV-2 was similar to that of SARS-CoV-1. Smither et al reported that SARS-CoV-2 is more stable at a medium RH of 40–60% (decay rate, 0.91%/min) compared with a higher RH of 68–88% (decay rate, 1.59%/min) in tissue culture media (TCM), whereas the converse was observed in artificial saliva, with a decay rate of 2.27% per minute at a medium RH and 0.40% per minute at a higher RH [ 29 ]. The results of the half-life obtained with TCM at a medium RH were similar to those described above [ 28 ].…”
Section: Environmental Factors Involved In Sars-cov-2 Inside Buildingmentioning
confidence: 99%
“…These results showed that the stability of SARS-CoV-2 was similar to that of SARS-CoV-1. Smither et al reported that SARS-CoV-2 is more stable at a medium RH of 40–60% (decay rate, 0.91%/min) compared with a higher RH of 68–88% (decay rate, 1.59%/min) in tissue culture media (TCM), whereas the converse was observed in artificial saliva, with a decay rate of 2.27% per minute at a medium RH and 0.40% per minute at a higher RH [ 29 ]. The results of the half-life obtained with TCM at a medium RH were similar to those described above [ 28 ].…”
Section: Environmental Factors Involved In Sars-cov-2 Inside Buildingmentioning
confidence: 99%
“…25 Experiments with aerosolised SARS-CoV-2 in artificial saliva have shown it to be twice as stable as influenza at medium humidity (40%-60%), and to have longer viability in high humidity (68%-88%) compared with lower humidities. 26 Interventions clinicians can undertake personally include self-distancing (eg, from a coughing patient) and careful doffing of personal protective equipment. Consideration should also be given to continuous masking by staff and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence on the airborne survival of SARS-CoV-2 was recently obtained by van Doremalen et al [53] and Smither et al [54] on different virus variants. van Doremalen et al [53] performed a bench-scale study in which both SARS-CoV-1 and SARS-CoV-2 were aerosolized, then the infectious viruses were quantified (TCID 50 / mL ).…”
Section: Survival Experimentsmentioning
confidence: 94%
“…Twelve papers performed experiments with coronaviruses at lab-scale with different aims: to evaluate performance of sampling methods [44][45][46][47][48] and to address the survival of coronavirus in experimental aerosolization scenarios [44,[49][50][51][52][53][54], also considering UV susceptibility [55].…”
Section: In Vitro Studies On Coronavirusmentioning
confidence: 99%
See 1 more Smart Citation